Factors Associated with Wash Behavior Using Theory Of Planned Behaviour Among Adolescents in Islamic Boarding School - Muthmainnah, Muthmainnah; Azzahra, Shoffiyah Hanin; Pratiwi, Damai Arum; Nurmala, Ira; Lin, Chung-Ying; Devi, Yuli Puspita; Nadia, Asma; Restuti, Dini Yulia (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2025)
Background: The behavior of Handwashing with Soap (HWWS) is a method of hand hygiene maintenance that protects oneself and those around from diseases. However, the habit of washing hands with soap might not be a routine practice among adolescent students in maintaining daily personal hygiene. The purpose of this study was to analyze the factors related to HWWS behavior among the students of Islamic boarding school based on the Theory of Planned Behavior (TPB). Method: This research was an observational study with a cross-sectional design. The sample consists of 104 students, aged 10 to 21 years old (53 male and 51 female) selected purposively. The data analysis conducted to assess the strength of relationships between four elements in the TPB and HWWS behavior as well using the contingency coefficient and Spearman correlation. Result: The results of the study show that behavioral intention was strongly associated with HWWS behavior (C = 0.609, p < 0.001). Meanwhile, the four TPB elements had moderate level of associations (C = 0.484 – 0.594, p < 0.001). To conclude, efforts are needed to improve HWWS facilities and strengthen HWWS behavior through programs tailored to the students' characteristics and needs.